Sistem Keamanan Rumah Menggunakan Sensor Passive Infrared - Wisnu Wiraditama; Dedi Candra; Ami Prasena Nugraha; Sulartopo Sulartopo (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2023)
The research discusses movement detection tools. This tool is designed to help homeowners detect movement that occurs at home when the homeowner is sleeping. Motion detectors or detectors are designed to help with home security systems. The pir sensor is used as a movement detector which sends notifications in the form of alarms. The method used in this research uses a prototype model process. The tool is made using a pir sensor and an arduino microcontroller board. Test results show that the response to movement is very good and is able to send sound notifications. The results of the research are the design of a pir sensor as a movement detector to help with the security system in the house.